A numerical method for the determination of dextrous workspaces of Gough-Stewart platforms - du Plessis, L. J.; Snyman, J. A. (International journal for numerical methods in engineering, 2001)
An optimization approach to the computation of the boundaries of different dextrous workspaces of parallel manipulators is presented. A specific dextrous workspace is the region in space in which, at each position of the working point, a manipulator can control the orientation of its upper working platform through a specified range of orientation angles. Here the dextrous workspace is determined from the intersection of suitably chosen fixed orientation workspaces, which are found by application of a constrained optimization algorithm. The procedure is simple and has the considerable advantage that it may easily be automated. The method is illustrated by its application to both a planar and spatial Gough–Stewart platform. Copyright © 2001 John Wiley & Sons, Ltd.